2022
DOI: 10.3389/fphys.2022.1004150
|View full text |Cite
|
Sign up to set email alerts
|

Flight performance of pollen starved honey bees and incomplete compensation through ingestion after early life pollen deprivation

Abstract: We investigated the effect of adult honey bee pollen nutrition on the flight performance of honey bees. Therefore, caged bees were allowed to perform 30 min of defecation/training flights every second day before flight performance of pollen-fed bees and pollen-deprived bees older than 16 days were compared in a flight mill. We first fed 10 µL of 1 M glucose solution to bees, and after they metabolized this during flight, they were fed 10 µL of 2 M glucose solution for a second flight test. Pollen-deprived bees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In a study like ours, the wet and dry weights of adult bees were reported to be 9.5-11.5 mg/bee and 3.6-4.0 mg/bee, respectively [57]. The worker bees were found to have lower wet and dry weights than the pollen-fed bees when they were not fed pollen until the 7th day after cell emergence [58].…”
Section: Hpg Developmentmentioning
confidence: 45%
“…In a study like ours, the wet and dry weights of adult bees were reported to be 9.5-11.5 mg/bee and 3.6-4.0 mg/bee, respectively [57]. The worker bees were found to have lower wet and dry weights than the pollen-fed bees when they were not fed pollen until the 7th day after cell emergence [58].…”
Section: Hpg Developmentmentioning
confidence: 45%
“…Thus, perhaps workers of captive colonies were consuming pollen directly from flowers to supplement their nutrition. Accordingly, honey bee workers that are initially pollen deprived, when later offered pollen, compensate by eating more pollen (Brodschneider et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, food shortage can decrease foraging efficiency in honey bees by reducing flight performance (Brodschneider et al, 2022) or foraging activity (Scofield & Mattila, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Foraging behaviour varies between individual pollinators and is dependent on the plant species visited (Willmer, 2011 ), but it can also be affected by land‐use‐induced limitation of floral resources. For example, food shortage can decrease foraging efficiency in honey bees by reducing flight performance (Brodschneider et al., 2022 ) or foraging activity (Scofield & Mattila, 2015 ). Additionally, poor nutrition can affect pollinator health, for example by reducing pollinator body size, which is directly linked to foraging behaviour and vice versa (Chole et al., 2019 ; Klumpers et al., 2019 ; Straub et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%